GROWTH AND BIOMASS RESULTS OF KALE (Brassica oleracea var. acephala) ON AQUAPONIC SYSTEM WITH APPLICATION OF THE RECIRCULATING AQUACULTURE SYSTEM PRINCIPLE - Amalia (Nim : 11414036), Astrid
Rapid growth in human population accompanied with the decrease of water and land resources causing the need for a new innovations in food supply. Aquaponic is a no land based cultivation system with a basic principles of utilizing water that contain fish wastes as a source of nutrition for hydroponic plant. Fish wastes will produce nutrition in the form of ammonia which is essential in plant growth and development. In conventional aquaponic systems, ammonia from fish wastes and fish feed residue can accumulate in the water used in the system and reach the concentration where it is toxic for the fish. Recirculating Aquaculture System or RAS can reduce the risks of ammonia accumulating in the water by changing it to nitrite and then nitrate which is not toxic for the fish. Kale is a vegetable that is increasing in popularity and demand as of late. This is because kale is a vegetable that rich in vitamin, mineral, fiber and other antioxidant component which are very healthy. This experiment aims to determine the plant growth rate and biomass results of kale cultivated in an aquaponic system with application of the recirculating aquaculture system principle. The aquaponics system used in this experiment consisted of four main components namely, fish tank, mechanic filter, biofilter, and hydroponic tank. The treatments carried out during the experiment was planting kale in two different components in one system which is, mechanic filter, with water of nutrition source directly from fish tank, and hydroponic tank, with water of nutrition source come that has passed through biofilter containing nitrifying bacteria. Kale planted with floating raft method at age 22 days after seedling and then harvested at age 55 days after seedlings. Growth and biomass result of kale were determined by measuring plant height and the amount of leaves each week until harvest, along with plant biomass and dry biomass immediately after harvest. According to the measurement at harvest, the average plant height for both treatment are 13,37 cm and 19,49 respectively,whlile the average amount of leaves are 8,28 and 8,35 respectively. Average of plant biomass results for both treatment are 3,06 gram and 2,8115 gram, while the dry biomass results are 0,283 gram and 0,247 gram. Those four measurements then tested statistically with unpaired t-test analysis ( = 0,05). The unpaired t-test statistic analysis results for all parameter in this experiment shows that the use of biofilter in the system does not give a significant effect to plant height, amount of leaves, plant biomass and dry biomass of kale.